The Romanization of Qurʾānic Letters: An Argument for a Review in Light of ʿIlm al-Tağwīd and Modern Arabic Linguistics - Jimoh, Shaykh Luqman (Al-Bayān, 2018)
More than ten Romanization schemes have been developed for Qurʾānic letters over time, and any transliteration of the Qurʾān follows one of these schemes. Islamic writers also adopt one of them when transliterating parts of the Qurʾān. Efforts were made in the past to develop a uniform system, but these have proved unsuccessful. This study highlights the need to harmonize such schemes and reviews the present transliteration methods for various Qurʾānic letters. It employs a descriptive method and reviews related library sources. In so doing, it demonstrates that there are various problems associated with having different transliteration schemes for Qurʾānic letters, and hence there is a need for a uniform scheme. It also shows that the transliteration of certain Qurʾānic letters do not, arguably, following the rules of both ʿIlm al-tağwīd and Modern Arabic linguistics, and so also calls for a review of the transliteration of those Qurʾānic letters in light of ʿIlm al-tağwīd and Modern Arabic linguistics.